Changes in Physical Properties of Hydrate Deposit during Hydrate Formation and Dissociation. Issue 1 (August 2020) - Zheng, Mingming; Wang, Xiaoyu; Wei, Meng; Wang, Kai; Liu, Tianle; Jiang, Guosheng
Abstract: The microscopic distribution pattern of hydrates in pores is closely related to the accuracy of seismic data and acoustic data in the exploration of hydrate resources, and has important influence on the permeability and mechanical stability of reservoirs during mining. This study performed macro-micro experiments of tetrahydrofuran (THF) hydrate formation and dissociation in solution and pore space. Dissociation characteristics of pore hydrate with different saturation and distribution pattern were observed, 2D and 3D models were built, fluid and quartz particle migration, channel blockage and reformation were captured and analysed. Results demonstrated that, as the concentration of THF in the solution increases from 19%, 24% to 29%, the main distribution pattern of the hydrate formed in the pores gradually changes from pore filling, particle cementation to skeleton supporting, while the dissociation behaviour of pore hydrate mainly happened at the pore filled area, particle surface and the particle connection area. As the saturation increases, the amount of water generated by dissociation increases, the more obvious the water migration, the greater the impact on the stability of the particles, and the more the formation of channels and blockages. During field methane recovery, controlling the dissociation rate of hydrates and fluid migration rate are helpful to maintain reservoir mechanical stability. Therefore, when temperature and pressure conditions are relatively stable, increasing the drainage channel can effectively reduce the turbulent oscillation, the impact on particle stability and blockage of sand production channel.